Correction of Serum Potassium Level in Hypokalaemic Patients with Hypomagnesaemia and Normomagnesaemia - Azfar Athar Ishaqui; Muhammad Liaquat Raza; Iyad Naeem Muhammad (KARACHI MEDICAL AND DENTAL COLLEGE, 2017)
Objective: To  determine the extent of increase in potassium level after intravenous infusion of potassium chloride in hypokalaemic patients  with  hypomagnesaemia  and  normomagnesaemia  and  to overview the impact of different concentrations and dilutions of potassium chloride infusion for rapid correction of hypokalaemia. Methods: A prospective, cohort study was conducted in Abbasi Shaheed Hospital, Karachi from January to March 2016. Convenience sampling was done, 46 patients were included who had a Serum Potassium level less than 3.5 meq/L at the time of admission to the hospital. Protocols of potassium  chloride infusion such as such as 20 mEq/200 ml, 30 mEq/300 ml, 40 mEq/400 ml and 50 mEq/500 ml were given  to  three  groups  of  hypokalaemic  patients  having  hypomagnesaemia, normomagnesaemia  and  hypermagnesaemia  to  figure  out  the  correlation  of  potassium  correction   with serum magnesium level. The pre and  post-infusion  serum  potassium  levels  were  checked along with the outcome of the extent of increase in potassium levels. Results: For 46 patients (mean age 60 ± 3 (r= 21-96 years), the mean pre-infusion serum potassium and magnesium levels were found to be 3.12 ± 0.04 (r= 2.30-3.5) mmol/L and 0.81 ± 0.03 (r= 0.52- 1.58) mmol/L respectively. The difference in the pre/post-infusion  serum  potassium  levels  in  hypokalaemic patients with hypomagnesemia (n=  46)  was  not  found  be  significant  (p>0.05)  whereas the pre/post-infusion serum potassium level was significant (p<0.05) in hypokalaemic patients with normomagnesaemia or hypermagnesaemia. Conclusion: Serum magnesium level needs to be concurrently monitored and corrected in mild to  moderate hypokalaemic patients as low magnesium levels were found to have profound effect on serum potassium level  in  patients  receiving  potassium  supplement  for  correction  of  potassium  level  back to normal.